Academic Resilience, Academic Stress, and Emotional Regulation as Predictors of Secondary School Students' Achievement in Chemistry in Anambra State - Samuel, Dr. Nkiru N.C.; Nnoli, Dr. Juliana Nkiru (Journal of Research in Industrial Technology and Educational Studies, 2025)
This study investigates the relationship between academic resilience, academic stress, emotional regulation, and chemistry achievement among secondary school students in Anambra State, Nigeria. Correlational survey research design was employed with a sample of 420 senior secondary school students (SS2) selected through stratified random sampling from government schools across three education zones with a total population of 27,530 SS2 students enrolled in the 148 public schools in the zones. Data were collected using standardized instruments: the Academic Resilience Scale (ARS-30), Perceived Academic Stress Scale (PASS), Cognitive Emotion Regulation Questionnaire (CERQ), and Chemistry Achievement Test (CAT). Multiple regression analysis revealed that academic resilience (β = 0.42, p < 0.001) positively predicted chemistry achievement, while academic stress (β = -0.31, p < 0.001) negatively predicted achievement. Adaptive emotional regulation strategies (β = 0.28, p < 0.01) positively predicted chemistry achievement, while maladaptive strategies (β = -0.19, p < 0.05) showed a negative relationship. Together, these variables accounted for 47% of the variance in chemistry achievement. Significant gender differences were found in academic resilience and adaptive emotional regulation, with female students scoring higher. The study concludes that interventions aimed at enhancing academic resilience, reducing academic stress, and promoting adaptive emotional regulation may improve chemistry achievement among secondary school students. The findings highlight the importance of psychological factors in science education and recommended the integration of psychological interventions into chemistry education to enhance student achievement
Keywords: Academic resilience; academic stress; emotional regulation; chemistry achievement; secondary education